Resolving Double Tax Treaty Disputes : The Challenges of Mutual Agreement Procedure with a Special Focus on Addressing the Concerns of Developing Countries in Africa — The South African and Ugandan Experience - Oguttu, Annet Wanyana (South African Yearbook of International Law, 2015)
Under contract law parties may agree, upon a breach of any of the provisions in the agreement, the aggrieved party may institute legal action to seek appropriate relief. A double tax treaty (DTA) is essentially an agreement between two contracting states that regulates the taxation of income derived from cross-border transactions of the residents of the two states, alleviates any impediments to cross-border transactions (for instance the double-taxation of income) as well as prevents any fiscal evasion and avoidance of income by such residents. When a country enters into a DTA with another country, generally, the treaty becomes part of the domestic tax law of that country. In South Africa, for instance, section 231(2) of the Constitution of the Republic of South Africa, 1996, read together with section 108(1) of the Income Tax Act,2 provides that as soon as the double tax treaty is ratified and is published in the Government Gazette, its provisions are effective as if they had been incorporated into the Income Tax Act.